Navigating National Identity Attachment: Social Representation of Indonesianness Among Muslim Communities in Yogyakarta - Muhammad Johan Nasrul Huda (LP2M UIN Sunan Kalijaga, 2026)
This study aims to investigate the dynamics of social representations of Indonesianness in a nation-state system characterized by negotiations between identities at the grassroots level. This study uses qualitative methods with applying phenomenology approach to seek the meaning of lived experiences related to national identity attachment among Muslim communities. Data collection used depth interviews for six participants who are prominent members of Muslim Communities in Yogyakarta. This study found that there are different types of social representation of Indonesianness among Muslim communities. Traditional and modern Muslims have many similarities in terms of social representation when compared to Salafi Muslims. Salafi Muslims share similar points of view with traditional and modern Muslims in representing the historical relationship between Islam, Yogyakarta, and Indonesianness, namely through the use of hegemonic representation. Traditional and Modern Muslims' interpretations of Indonesianness represent optimism and positive view. In contrast, Salafi Muslims used polemical representations to explain their strategies for managing Indonesianness, their perceptions of Indonesia, and their imagination of Indonesia in the future. Moreover, they stated that sharia should be applied comprehensively for making Indonesia meaningful. This can been seen that national identity attachment is a dynamic process that is influenced by perception about Islam, and the history of Yogyakarta and Indonesia.